2019
DOI: 10.1126/science.aav3384
|View full text |Cite
|
Sign up to set email alerts
|

Demographic dynamics of the smallest marine vertebrates fuel coral reef ecosystem functioning

Abstract: How coral reefs survive as oases of life in low-productivity oceans has puzzled scientists for centuries. The answer may lie in internal nutrient cycling and/or input from the pelagic zone. Integrating meta-analysis, field data, and population modeling, we show that the ocean’s smallest vertebrates, cryptobenthic reef fishes, promote internal reef fish biomass production through extensive larval supply from the pelagic environment. Specifically, cryptobenthics account for two-thirds of reef fish larvae in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
185
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(193 citation statements)
references
References 79 publications
5
185
1
2
Order By: Relevance
“…; Brandl et al . ). We demonstrate that reef systems can be bottom‐heavy in areas of high irradiance, and middle‐driven when external energetic subsidies, delivered by a panoply of biophysical processes, are maximized.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Brandl et al . ). We demonstrate that reef systems can be bottom‐heavy in areas of high irradiance, and middle‐driven when external energetic subsidies, delivered by a panoply of biophysical processes, are maximized.…”
Section: Discussionmentioning
confidence: 97%
“…It has also become clear that small‐bodied cryptic fishes, such as blennies and gobies, are key energetic resources sustaining overall reef fish production (Brandl et al . ). Because of their low detectability in visual surveys (Kulbicki et al .…”
mentioning
confidence: 97%
“…Protection of reefs requires effective management plans that can mitigate the negative impacts of local and global stressors and conserve ecosystem functioning. Much is known about the major threats to coral reefs, including climate change and overfishing (Graham et al 2015;Bruno et al 2019), and several key species living on coral reefs have been identified (Bellwood et al 2004;Alvarez-Filip et al 2009;Brandl et al 2019). However, there is much less clarity about what exactly a functioning coral reef is and how it is influenced by the hyperdiverse communities that make coral reefs one of the most remarkable ecosystems on the planet.…”
Section: Front Ecol Environmentioning
confidence: 99%
“…; Brandl et al . ). However, there is much less clarity about what exactly a functioning coral reef is and how it is influenced by the hyperdiverse communities that make coral reefs one of the most remarkable ecosystems on the planet.…”
mentioning
confidence: 97%
“…Recently, marine fish communities underwent a climate‐driven functional switch from fast to slow life‐history species dominance (McLean, Mouillot, Goascoz, Schlaich, & Auber, ). In coral reefs, shifts from species with small body size and fast lifespan to large‐bodied and slow life‐history dominance can disrupt food chains (Hempson, Graham, MacNeil, Hoey, & Almany, ) and severely decrease ecosystem productivity (Brandl et al, ). Therefore, understanding the impacts of habitat changes in coral reefs fish communities from fine to coarse spatial scales is critical for predicting how the ecological process will respond to increasing large‐scale disturbances.…”
Section: Discussionmentioning
confidence: 99%